2019
DOI: 10.1186/s13256-019-2221-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary effusion lymphoma in a human immunodeficiency virus-negative patient with unexpected unusual complications: a case report

Abstract: Background Primary effusion lymphoma is a rare, high-grade non-Hodgkin’s lymphoma that usually occurs in immunosuppressed or human immunodeficiency virus-positive individuals in advanced stages of the disease. However, primary effusion lymphoma occasionally affects immunocompetent patients who are infected with human herpes virus type 8 or Epstein-Barr virus. This disease manifests with liquid collections in cavities, producing constitutional symptoms; fever; weight loss; and symptoms related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…We included 74 studies in the final analysis, accounting for 105 individual patient cases. Over the 23-year period of publications, 32 studies were published during the first 12 years (1995–2008) 3 , 6 , 10 39 and 42 during the second 11 years (2009–2020) 40 81 as full articles (n=58), letters (n=7), images (n=5), and conference papers/abstracts (n=4). Sixty-eight (91.9%) articles reported one or two cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 74 studies in the final analysis, accounting for 105 individual patient cases. Over the 23-year period of publications, 32 studies were published during the first 12 years (1995–2008) 3 , 6 , 10 39 and 42 during the second 11 years (2009–2020) 40 81 as full articles (n=58), letters (n=7), images (n=5), and conference papers/abstracts (n=4). Sixty-eight (91.9%) articles reported one or two cases.…”
Section: Resultsmentioning
confidence: 99%
“…Demographics for 105 patients and clinical characteristics are listed in Table 1. The median (interquartile range, IQR) age was 77 (69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85) with no gender difference (P>.05). The male-to-female ratio was 6:1.…”
Section: Patient Demographics Comorbidities and Pel Sitementioning
confidence: 99%
“…The typical cytological features of PEL are large, multinucleated or multilobed lymphoid cells with prominent nucleoli, basophilic cytoplasm with clear small vacuoles, and high mitotic activity. Immunophenotypically malignant cells express CD45+ and are negative for B‐cell markers (CD19, CD20, and CD79a) and T‐cell markers (CD3, CD4, CD8), respectively 1 …”
Section: Discussionmentioning
confidence: 99%
“…Immunophenotypically malignant cells express CD45+ and are negative for B-cell markers (CD19, CD20, and CD79a) and Tcell markers (CD3, CD4, CD8), respectively. 1 Molecular studies have reported PEL cell of origin is derived from postgerminal center B-cells approaching plasma cell differentiation. 5,9 This explains the frequent expression of activation markers like CD30 and plasma cell markers such as CD38, CD138, and EMA in PEL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation